A Novel Coating of Orthodontic Archwires with Chlorhexidine Hexametaphosphate Nanoparticles - Al-Fadhily, Zahraa Mohammed; Abdul-Hadi, Mehdi (International Journal of Biomaterials, 2023)
Statement of the Problem. The use of orthodontic fixed appliances may adversely affect oral health leading to demineralizing lesions and the development of gingival problems. Aims of the Study. The study aimed to coat orthodontic archwires with chlorhexidine hexametaphosphate nanoparticles (CHX-HMP NPs) and to evaluate the elusion of CHX from CHX-HMP NPs. Materials and Methods. A solution of CHX-HMP nanoparticles with an overall concentration of 5 mM for both CHX and HMP was prepared, characterized (using atomic force microscope and Fourier transformation infrared spectroscopy), and used to coat orthodontic stainless steel (SSW) and NiTi archwires (NiTiW). The coated segments were characterized (using scanning electron microscopy SEM with energy dispersive X-ray spectrometry and field emission SEM) and subjected to the elusion assessment. Results. After having their composition validated, the average size of the CHX-HMP NPs was assessed to be 51.21 nm, and the analysis revealed that the particles had both chlorine and phosphorus. After 30 minutes in the coating solution, NPs deposited on the surface of the SSW and NiTiW. A continuous release of soluble CHX in artificial saliva was detected from both SSW and NiTiW as long as the experiment lasted for 28 days without reaching a plateau. However, the release from coated NiTiW was significantly more than coated SSW at 7, 14, and 28 days. While at day 21, the release from coated SSW was slightly greater than that from the coated NiTiW. Conclusion. Orthodontic stainless steel and NiTi archwires can be successfully coated with CHX-HMP NPs and give sustained release of CHX along the examined period.